Educação ambiental para uma cultura de paz contribuições para a formação de professores - Mello, Caroline Castro de (2014)
This dissertation, or constructive dissertation of a research desire, had its creation by entering the course of Master s degree in Education of the Program of Post-degree in Education of the Federal University of Santa Maria. It founds itself registered in the Research Line: Formation, Knowledge and Professional Development, under the topic of Environmental Education. By associating it to the achievement of a dream, we did not list research problems, but wishes, having as its main desire to investigate: How do we, teachers, can work with environmental education for a peace culture? We long to reach this desire through a qualitative research. Therefore, we draw possible ways to reach that desire. The paths we intend to course to investigate how the Environmental Education can encourage the peace culture at school, our researches main goal, will be drawn with the assistance of bibliographic resources and teacher practice experiences. With this support, there were produced educational strategies that were developed to work the environmental education and the peace culture. Such strategies include the task of working with mandalas and circular dances and were developed with the academics of licentiate courses of UFSM. Through this path it was possible to realize that in order to make a welcoming, respectful environment, that includes the environmental and peace values, those values need to be lived. In that sense, it is not possible to offer something you do not own, therefore, the answer to our research desire was found in the need of working the self-knowledge, so that we can discover our own path, and understand that the process of the teacher formation is permanent.